1991
DOI: 10.1063/1.106182
|View full text |Cite
|
Sign up to set email alerts
|

High quality (111)B GaAs, AlGaAs, AlGaAs/GaAs modulation doped heterostructures and a GaAs/InGaAs/GaAs quantum well

Abstract: We report the successful growth of high quality molecular beam epitaxy (MBE) GaAs, AlGaAs, AlGaAs/GaAs modulation doped heterostructures and a GaAs/InGaAs/GaAs quantum well on GaAs (111)B substrates. Modulation doped heterostructures show a 77 K mobility of 145 500 cm2/V s with a sheet density of 5.0×1011 cm−2. Photoluminescence of (111)B GaAs indicates a lower carbon incorporation than achieved on (100) substrates. The low growth temperature and high material quality obtainable in (111)B growth will provide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…Miscut samples are prevalent in the literature, for example (111) GaAs/AlAs growth has been shown to have superior morphology with a miscut angle from 0.5 • to 4 • and in general, intentional miscuts improve growth quality due to slip-step growth [69][70][71][72] . In Si, recently investigated hydrogen terminated (111)Si miscut surfaces have shown very high mobility 73 and the wafer miscut is expected to break the valley degeneracy 43,74 .…”
Section: Valley Degeneracy In Miscut Samplesmentioning
confidence: 99%
“…Miscut samples are prevalent in the literature, for example (111) GaAs/AlAs growth has been shown to have superior morphology with a miscut angle from 0.5 • to 4 • and in general, intentional miscuts improve growth quality due to slip-step growth [69][70][71][72] . In Si, recently investigated hydrogen terminated (111)Si miscut surfaces have shown very high mobility 73 and the wafer miscut is expected to break the valley degeneracy 43,74 .…”
Section: Valley Degeneracy In Miscut Samplesmentioning
confidence: 99%
“…1(c)]. To avoid hillock formation, many groups have adopted the use of offcut substrates, which promote step flow growth rather than 3D islanding, 58,[65][66][67][68] but the optimization of growth conditions is seldom reported, and smooth growth remains challenging. [69][70][71] Furthermore, much of the early work on (110) and (111) growth was performed prior to widespread availability of commercial AFMs and so morphology studies were often limited to optical microscopy.…”
Section: B Challenges In Iii-v Growth On (111) and (110) Substratesmentioning
confidence: 99%
“…69 However, growth of smooth indium-containing materials such as InGaAs (111)B, under these same reconstructions, is difficult due to the high desorption rate of indium above T g ¼ 530 C. 85,86 Due to these challenges, the use of offcut substrates became the primary solution to achieve smooth GaAs(111)B growth. 66,67,85 Yang et al identified that the hillocks formed on GaAs(111)B were composed of three vicinal (111) "facets" inclined $2 from the singular plane. 85 They proposed that these vicinal facets were more energetically stable than the singular (111) plane and thereby demonstrated that tilting the surface toward these planes by 1 -3 in the h211i directions promoted smooth growth.…”
Section: Ingaas(111)a: Summarymentioning
confidence: 99%
“…However, recently this problem has been overcome and good quality, reproducible growth has been achieved using conventional molecular beam epitaxy ͑MBE͒. 13,19,20 A few strain relaxation studies have been published. Anan et al 21 have determined the critical thickness of the InGaAs/GaAs͑111͒B heterostructures, with a misorientation of 2°towards ͓011͔ and high In contents of 0.4-0.6, by measuring the surface lattice parameter changes using reflection high energy electron diffraction ͑RHEED͒ streak separation.…”
Section: Introductionmentioning
confidence: 99%